Lung cancer risk between maternal and paternal half-siblings points to main environmental causation and targets for prevention - Hemminki, Kari; Zitricky, Frantisek; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli (Lung cancer (Amsterdam, Netherlands), 2025)
INTRODUCTION: Familial risk of lung cancer (LC) is at the level of many common cancers (ca 2.0) but as cigarette smoking is the main cause of LC, it has remained undefined to what extent smoking contributes to the familial risk. We take advantage of the natural experiment of divorce. In Sweden, it has been customary that children stay with their mother after divorce. We thus hypothesize that only maternal half-siblings share the childhood environment to the same extent than full siblings. METHODS: We used Swedish nation-wide data on family structures and cancers up to year 2021 to determined LC risk (standardized incidence ratio, SIR with 95% confidence intervals) in maternal and paternal half-siblings and in full siblings. RESULTS: Familial risk for LC in maternal half-siblings was 2.21 (1.76-2.77) which was not different from that of full siblings 2.23 (2.22-2.44). For paternal half-siblings the risk was 1.56 (1.21-2.01). For adenocarcinoma the risks were for full siblings 2.36 (2.23-2.51), for maternal half-siblings 2.55 (1.93-3.35) and for paternal half-siblings 1.33 (0.94-1.87). CONCLUSIONS: The results showed that familial risk for LC was equal in full siblings and in maternal half-siblings; the risks for paternal half-siblings were lower and for adenocarcinoma significantly lower than those for full siblings. The results suggest that smoking is a major contributor to familial risk of LC in this setting. Smoking starts at an early age and anti-smoking campaigns should target childhood environment for prevention of smoking initiation.
Keywords: Fathers; senioři; otcové; kouření; Familial cancer; Incidence; Middle Aged; mužské pohlaví; nádory plic; incidence; sourozenci; Adult; Sweden; Adenocarcinoma; Smoking; Childhood environment; ženské pohlaví; Humans; Mothers; matky; Maternal half-sibling; lidé středního věku; Siblings; rizikové faktory; dospělí; Švédsko; Female; Risk Factors; Aged; Lung Neoplasms; lidé; Male